Uncompleted project of the Central Municipal Park in Lublin - Boguszewska, Kamila Lucyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The areas of the former Royal Pond (Staw Królewski) in Lublin were the subject of many projects and architectural competitions. Over the years the concepts of development of this area have been changing, but both in the pre-war period and later, it was supposed to be green urban space accessible to the residents. The aim of the article is to outline the development plans of the city of Lublin (second half of the 20th century / beginning of the 21st century) concerning the implementation of the Central Municipal Park, which was planned in the area of the former pond. The works on this project, which was finally never implemented, have been carried out since the end of the 1950s. This name, used interchangeably with Culture Park (Park Kultury), appeared for the first time in the General Spatial Development Plan for the city of Lublin in 1957. The author, on the basis of conducted research, archival queries and comparative studies, analyses the ideas and solutions concerning the development of this part of the Bystrzyca river valley.